Zmiany w polskim systemie ochrony lotnictwa cywilnego - Łukasz Szymankiewicz (Przegląd Geopolityczny)
Air transport, as a component of critical infrastructure, is an attractive target for terrorist attack, which makes it necessary to maintain an adequate level of aviation security. An important element of protection is the personnel training system, in which changes are made in response to the dynamics of threats, including the evolution in the motivation and modus operandi of terrorists. The aforementioned evolution of security threats is a result of modern migration processes and cultural changes that promote radicalization and political extremism. The purpose of the article is to present and evaluate the changes in the National Training Program on civil aviation security, with a particular focus on the introduction of the topic of countering internal threats, including radicalization, the introduction of a new cybersecurity training, as well as concerning the expansion of the categories of people covered by the training on civil aviation security awareness.